THE USE OF PRONUNCIATION BINGO GAME TO IMPROVE STUDENTS’ PRONUNCIATION - Ahmad Suhaili; Asep Kurniawan (FKIP, Universitas Banten Jaya, 2019)
This research is mainly purposed to find out whether there is influence of using pronunciation bingo game to improve students’ pronunciation at first grade in MTs Alkhaeriyah Kepandean Ciruas Serang. The game is applied by experiment class and control class. The method of this research is true-experiment research. The population in this research is the first grade in MTs Alkhaeriyah Ciruas Serang. The writer took three classes with total number of the first grade are 132 Students. They are three classes, 44 Students from class VIIA and 44 Students from class VIIB and 44 Students from class VIIC. The writer took 60 students as sample and uses random sampling because the writer uses true-experiment method. To analyze this research the writer uses T-test method and to get the data the writer uses observation technique, and test as instrument of research. The observation is to know the students’ pronunciation at the first grade in MTs Alkhaeriyah Keoandean Ciruas Serang, while, test is to know the influence use of pronunciation bingo game to improve students’ pronunciation at the first grade in MTs Alkheriyah Kepandean Ciruas Serang. After having analysis data, there is influence using of pronunciation bingo game to improve students’ pronunciation between experiment class and control class, based on the calculation is know that t table with level significance 5 % = 2,00 and with level significance 1% = 2,65 so tobservation n = 20,34 > t table = 2,00 or tobservation n = 20,34 > t table = 2,65.the conclusion is that the writer reject H0 : to < tt . It means there is no influence the use of pronunciation bingo game to improve students’ pronunciation at the first grade in MTs Alkhaeriyah Kepandean Serang and receive Ha : to > tt. it means there is influence the use of pronunciation bingo game to improve students’ pronunciation at the first grade in MTs Alkhaeriyah Kepandean Ciruas Serang.